1994
DOI: 10.1021/ef00043a005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cation-exchange iron for catalytic liquefaction of a subbituminous coal

Abstract: The total conversion and the oil yield in liquefaction tests of iron ion-exchanged Black Thunder coal were found to increase by up to 23 and 18%, respectively, relative to the untreated coal. The ion-exchanged coal samples were prepared by stirring a slurry mixture of the coal and ferric acetate [Fe(OOCCH3)3] in a 10-L fermenter. The ion-exchange process, in which iron was exchanged primarily for calcium and magnesium, yielded a highly dispersed catalytic iron species for coal liquefaction. 57Fe Mossbauer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…229 In the case of low rank coals, ion exchange procedures have been used to replace surface carboxyl-bound calcium or magnesium ions by iron ions, which under liquefaction conditions are converted to highly dispersed and catalytically active iron species. 230,231 Kaneko et al reported that a synthetic g-FeOOH catalyst (lepidcrocite) exhibited an excellent liquefaction activity because of its transformation into smaller crystallite size of pyrrhotites (Fe 1Àx S) under liquefaction conditions. 212,232,233 Naturally available limonite (a-FeOOH) ores were pulverized and used as catalysts for the liquefaction of coal.…”
Section: Dissolution Catalystsmentioning
confidence: 99%
“…229 In the case of low rank coals, ion exchange procedures have been used to replace surface carboxyl-bound calcium or magnesium ions by iron ions, which under liquefaction conditions are converted to highly dispersed and catalytically active iron species. 230,231 Kaneko et al reported that a synthetic g-FeOOH catalyst (lepidcrocite) exhibited an excellent liquefaction activity because of its transformation into smaller crystallite size of pyrrhotites (Fe 1Àx S) under liquefaction conditions. 212,232,233 Naturally available limonite (a-FeOOH) ores were pulverized and used as catalysts for the liquefaction of coal.…”
Section: Dissolution Catalystsmentioning
confidence: 99%
“…Dispersion can be enhanced by impregnating the coal particles with water-or oil-soluble catalyst precursors such as metal salts or naphthenates, acetylacetonates and carbonyls. In the case of low-rank coals (lignite, brown coal, sub-bituminous coals), ion-exchange procedures have been used to replace surface carboxylbound calcium or magnesium ions by iron ions, which under liquefaction conditions are converted to highly dispersed and catalytically active iron species [97,108,109]. Under appropriate conditions, the high dispersion of the precursor is maintained during the in situ transformation to the active catalyst phase, whereas agglomeration can occur by using physical mixtures of precursor and coal [9,97,[99][100][101]107].…”
Section: Catalysis In Direct Coal Liquefaction 3031mentioning
confidence: 99%
“…Upon liquefaction of Morwell brown coal, upgrading reaction, such as the decrease of dichloromethane insoluble yield, was enhanced by exchange of several kinds of cations (Sn, Fe [3,4], Co, Ni, Zn, and Pb [4]). Compared with liquefaction of lignite, brown or subbituminous coal with any one of Fe 2 O 3 [5,6], FeCl 2 [7], and pyrite [8] additive, it was also reported that upgrading reaction, such as the decrease of tetrahydrofuran (THF) insoluble yield, was enhanced on that of Fe 2+ exchanged lignite or coal. In comparison with liquefaction of demineralized Adaro subbituminous coal with tetralin plus elemental sulfur at 420°C, the authors have reported that upgrading of coal, such as the decrease of residue (acetone insoluble) yield and the increase of oil (hexane soluble) yield, occurred significantly upon liquefaction of coal exchanged with several kinds of cations (Co 2+ , Ni 2+ and Fe 2+ ) to coal [9].…”
Section: Introductionmentioning
confidence: 99%
“…6 bituminous coal, resulting in high coal conversion and high oil yield [12]. Upon hydrocracking of a pentane insoluble constituent obtained after liquefaction of Point of Ayr bituminous coal, Mo(CO) 6 and W(CO) 6 exhibited greater catalytic activity than Fe(CO) 5 and Cr(CO) 6 [13].…”
Section: Introductionmentioning
confidence: 99%